Implementation of a campus-based and peer-delivered HIV self-testing intervention to improve the uptake of HIV testing services among university students in Zimbabwe: the SAYS initiative - Fadzai Mukora-Mutseyekwa; Paddington Tinashe Mundagowa; Rugare Abigail Kangwende; Tsitsi Murapa; Mandla Tirivavi; Waraidzo Mukuwapasi; Samantha Nokuthula Tozivepi; Charles Uzande; Queen Mutibura; Elizabeth Marian Chadambuka; Mazvita Machinga (BMC, 2022)
Abstract Background The uptake of HIV testing services among adolescents and young adults in Zimbabwe is low due to stigma associated with the risk of mental and social harm. The WHO recommends HIV self-testing (HIVST) as an innovative approach to improve access to HIV testing for this hard-to-reach populations. This study describes the development and implementation of a coordinated multifaceted and multidisciplinary campus-based approach to improve the uptake of HIV testing among university students in Zimbabwe. Methods We utilized both quantitative and qualitative methods guided by the Exploration, Preparation, Implementation, and Sustainment Framework. A formative survey, in-depth interviews, and a scoping review were conducted as part of the situation analysis. Implementers (peer educators and health workers) were trained and community dialogue sessions were conducted to ascertain the determinants (enablers and barriers) influencing both the inner and outer contexts. Self-test kits were disbursed over 6 months before a summative evaluation survey was conducted. Qualitative data were analyzed thematically while the chi-squared test was used to analyze quantitative data. Results The formative evaluation showed that 66% of students intended to test and 44% of the enrolled students collected HIVST test kits. Giving comprehensive and tailored information about the intervention was imperative to dispel the initial skepticism among students. Youth-friendly and language-specific packaging of program materials accommodated the students. Despite the high acceptability of the HIVST intervention, post-test services were poorly utilized due to the small and isolated nature of the university community. Implementers recommended that the students seek post-test services off-site to ensure that those with reactive results are linked to treatment and care. Conclusions Peer-delivered HIVST using trained personnel was acceptable among adolescents and young adults offered the intervention at a campus setting. HIVST could increase the uptake of HIV testing for this population given the stigma associated with facility-based HTS and the need for routine HIV testing for this age group who may not otherwise test. An off-site post-test counseling option is likely to improve the implementation of a campus-based HIVST and close the linkage to treatment and care gap.